Jeffrey Kurtzman: Approaches to Monteverdi. Aesthetic, Psychological, Analytical and Historical Studies. Padstow 2013 - Bartłomiej Gembicki (Muzyka)
Recenzja ksiązki: Jeffrey Kurtzman, Approaches to Monteverdi. Aesthetic, Psychological, Analyticaland Historical Studies